What Type of Contracts Underlie Aggregate Wage Dynamics? - Jadresic, Esteban (IMF Working Papers; Working Paper ;, 1997)
This paper shows that it is possible to estimate the importance of different types of wage contracts at the aggregate level using the same data used to estimate standard Phillips curves. It finds that the behavior of the Chilean private aggregate wage during the 1980s is well described by two-year contracts that are revised every six months according to 100 percent of past inflation. The estimates also show that the unemployment rate was a strong determinant of the contract's target real wage and that most wage negotiations were carried through during the first half of every year. The results prove robust to a variety of tests and fit the data better than standard Phillips curves.